Investigação da eficiência da degradação oxidativa por via direta e indireta de corantes empregados na indústria têxtil com o ozônio gerado eletroquimicamente - Franco, Débora Vilela (2005)
The direct (ozone), indirect (hydroxyl radical) and mixed (O;,/HO*) oxidation of synthetic eliluents containing reactive vellovv 143 (RY 143) or reactive blue 264 (RB 264). both dyes widely uscd in the texlile industry. were investigated by changing the pW and the dye concentration of the solution. The concentration in the gaseous phases (O2 + O3) of the elecirochemicallv generated ozone in the reactor previously developed by the heterogeneous electrocatalysis research group. was maintained constant during all the experiments. The degradation of dyes was monitored as function of ozonation time by UV/Vis spectroscopy. total organic carbon (TOC) and Chemical oxygen demand (COD). Additionally, organic and inorganic anions were qualitatively analyzed by HPLC'. Spectrophotometric results support decolorization process depends on pH solution and Chemical nature of dyes. TOC and COD data. support the degradation process depends on pH being. however. little affected by the Chemical nature of dyes. Indirect oxidation by HO* (/;H = 12) is the more efficient process to remove the color and total carbon from the effluent. HPLC results reveal oxalate and formate as the main degradation products during ozonation. Decoloration kinetic data reveal most kinetic curves present two linear segments following the pseudo-first order model with respect to ozone or hidroxil radical. A reaction model was proposed to explain the decoloration kinetics. The analysis of the pseudo-first order kinetic constants. as function of p\-\ and reaction time. permitted to evaluate the contribution of the direct and indirect oxidation process during the ozonation process